Melhoria de processo de acompanhamento, controle e transparência de resultados de concursos e seletivos públicos da Universidade Federal do Maranhão - ARRUDA, Ana Carla Araújo (2024)
Technology plays a transformative role in different segments of society and in public administration it has become increasingly important, ratifying its modernizing character by improving government services, optimizing processes, improving communication, increasing productivity and reducing errors. At the Federal University of Maranhão (UFMA), the management of candidate nomination and induction processes is carried out through manual controls in the Pro-Rectory of People Management unit (PROGEP), which tends to make these processes less efficient. In this work we present the proposal to develop process improvements with a focus on information management solutions for public and selective competitions at UFMA, through mapping and improvement of processes, customization of the competition module in the SIGRH system and the implementation of a module on the website of PROGEP with a focus on disseminating information about UFMA competitions and selection processes. As for the methodology, applied and bibliographical research is used. To achieve the main objective, documentary research of norms and resolutions, application of a research questionnaire in other universities, modeling of candidate nomination processes and meetings with actors involved in the customization processes of the SIGRH system and website were carried out. PROGEP. Process mapping and modeling were completed, as was the application of the questionnaire. The results present the elaboration of the improvement that includes the customization and the development of new functionalities of SIGRH. It is concluded that in order to guarantee the achievement of the objective proposed in this work, it will be necessary to have the support of all actors involved in the process, as well as the University managers.